2014
DOI: 10.1186/1478-4491-12-48
|View full text |Cite
|
Sign up to set email alerts
|

The influence of rural clinical school experiences on medical students’ levels of interest in rural careers

Abstract: BackgroundAustralian Rural Clinical School (RCS) programmes have been designed to create experiences that positively influence graduates to choose rural medical careers. Rural career intent is a categorical evaluation measure and has been used to assess the Australian RCS model. Predictors for rural medical career intent have been associated with extrinsic values such as students with a rural background. Intrinsic values such as personal interest have not been assessed with respect to rural career intent. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 22 publications
6
41
0
Order By: Relevance
“…29 Students completing a rural or remote clinical placement are more positively inclined towards working rurally upon graduation, potentially contributing towards an easing of ongoing workforce shortages. 30 The shift in geographical profile of clinical placements may also be influenced by the increasing number of tertiary institutions offering physiotherapy training programs in metropolitan areas. Rising student numbers creates an increasing demand for clinical placements, resulting in greater competition for available placements.…”
Section: (1)mentioning
confidence: 99%
“…29 Students completing a rural or remote clinical placement are more positively inclined towards working rurally upon graduation, potentially contributing towards an easing of ongoing workforce shortages. 30 The shift in geographical profile of clinical placements may also be influenced by the increasing number of tertiary institutions offering physiotherapy training programs in metropolitan areas. Rising student numbers creates an increasing demand for clinical placements, resulting in greater competition for available placements.…”
Section: (1)mentioning
confidence: 99%
“…[14] Although rural training is usually done in places with limited resources, absence of the internet and web-based support has been found to increase students' perception of academic isolation. [15] Our results showed that limited resources contributed to negative rural experiences. Students recommended that in future rural training sites should be equipped with adequate resources and facilities, such as electricity, water, television and internet.…”
Section: Discussionmentioning
confidence: 67%
“…No admission schemas have been convincingly related to better health outcomes. Positive career uptake data exist unequivocally for three programmes that were designed for such an achievement, and many admission policies have been validated by examining career intentions and career locations …”
Section: Background To the Literature Review And Analysismentioning
confidence: 99%